Antibacterial and antioxidant activities of Anethum graveolens L. dried fruit extracts - Keerati Tanruean (2018)
Essential oil fraction (EOF), deodorized hot water fraction (DeHWF) and methanol fraction (MeF) of Anethum graveolens L. were evaluated for their antibacterial activity against seven pathogenic bacteria by disc-diffusion and micro-well dilution methods. The EOF exhibited antibacterial activity against five pathogenic bacteria (E. faecalis, K. pneumoniae, S. aureus, S. epidermidis and S. typhi), while the DeHWF and the MeF were inactive. S. epidermidis was the most sensitive strain inhibited by EOF (MIC 0.25 mg/mL). Furthermore, antioxidant properties of the EOF, the DeHWF and the MeF based on free radical scavenging activity and lipid peroxidation inhibition, were also evaluated. The MeF displayed the highest level of DPPH radical scavenging (IC50 22.3 μg/mL) while the DeHWF exhibited the highest inhibition of lipid peroxidation inhibiton (IC50 4.7 μg/mL). High amounts of phenolic compounds were found in the DeHWF (35.1 mgGAE/gextract) and the MeF (22.1 mgGAE/gextract), while the EOF contains low amount (9.5 mgGAE/gextract). Moreover, a high content of chlorogenic acid (6.04 μg/gextract) was found in the DeHWF. The chemical compositions of the EOF were analyzed by gas chromatography-mass spectrometry (GC/MS). Twenty two constituents were detected and the major components were D-carvone, dillapiole and L-limonene.